2010
DOI: 10.1007/s00125-010-1999-y
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative cost of prescription medication in outpatients with type 1 diabetes in Finland

Abstract: Aims/hypothesis We examined the 11-year cumulative outpatient cost of prescription medication in patients with type 1 diabetes by subgroups according to the presence of complications and duration of diabetes. Methods This longitudinal study included a nationally representative cohort of patients with type 1 diabetes (N=3,717) from the Finnish Diabetic Nephropathy Study (FinnDiane). The data were linked to the Drug Prescription Register. The cumulative cost was calculated between 1998 and 2008. Information on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Acute symptoms can be controlled by insulin injections, but the diabetes-related disease burden increases with time due to chronic complications (Lithovius et al 2011). An estimated third of patients with long-standing type 1 diabetes are affected by kidney disease, which is characterized by increased urinary albumin excretion, high blood pressure and a gradual decline in glomerular filtration (Gross et al 2005; Mäkinen et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Acute symptoms can be controlled by insulin injections, but the diabetes-related disease burden increases with time due to chronic complications (Lithovius et al 2011). An estimated third of patients with long-standing type 1 diabetes are affected by kidney disease, which is characterized by increased urinary albumin excretion, high blood pressure and a gradual decline in glomerular filtration (Gross et al 2005; Mäkinen et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes was defined by time of diagnosisless than 40 years, C-peptide less than or equal to 0.3 nmol/L or starting insulin treatment within one year of diagnosis if C-peptide was not measured andpositive anti-glutamate decarboxylase antibody (anti-GAD), islet cell or insulin antibodies. 25,26,27 The inclusion criteria are being male with T1DM with duration of more than ten years. Those patients with chronic kidney disease, age below 16 years, duration of diabetes less than ten years, and those who are smokers were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The present study is part of the nationwide multicenter prospective Finnish Diabetic Nephropathy Study (Finn-Diane) with the aim to identify risk factors for diabetic complications. A more detailed description of the study has been reported in previous publications [3,13]. Briefly, all adult patients with type 1 diabetes from more than 70 hospitals and primary health centres across Finland were asked to participate.…”
Section: Methodsmentioning
confidence: 99%
“…These patients are also likely to display co-morbidities, requiring multiple pharmacological therapies. Our previous study showed that ESRD multiplies prescription medication costs in patients with type 1 diabetes [3]. Compared to dialysis, kidney transplantation provides a better alternative: it prolongs survival, improves quality of life and offers cost-effective treatment for ESRD [2,4,5].…”
Section: Introductionmentioning
confidence: 99%